Study and Comparison of the Performance of Passive UHF RFID Tags in the Presence of Mutual Coupling - Fernand, Gbamélé Konan; Edouard, Akpata; Daniel, Assamoi Claude (Research and Developments in Engineering Research Vol. 2, 2023)
The objective of this paper is to study and compare the performance of some prototype commercial passive UHF RFID tags such as the printed Dipole, the printed T-Match and the printed Meander dipole as a function of their sensitivity to mutual coupling. In practical applications, mutual coupling changes the intrinsic parameters of the antennas attached to these tags, i.e. change in the impedance of the tags, distortion of the radiation pattern. This results in the non-reading of some and the degradation of the reader-tag link budget thus reducing the performance of passive UHF RFID tags. The communication performance of UHF RFID systems depends on the relative position of the tags. In this work, we analyze the performance of printed tags using ANSYS HFSS software to directly extract the mutual impedance values in various scenarios and then compare the sensitivity levels to mutual coupling with MATLAB software. The simulated outcomes show the effectiveness of this study in providing a thorough insight of tag performance. These outcomes open up new avenues of research into the study of mutual coupling between tags and will help users make better decisions in the selection of UHF RFID tags for radio frequency identification of products.